Advances in Metal Halide Perovskite Scintillators for X-Ray Detection - Wang, Ting; Zeng, Guoqiang; Yang, Yang Michael; Yang, Zhi; Wang, Tianchi; Li, Hao; Han, Lulu; Yu, Xue; Xu, Xuhui; Ouyang, Xiaoping (Nano-Micro Letters, 2025)
The relentless pursuit of advanced X-ray detection technologies has been significantly bolstered by the emergence of metal halides perovskites (MHPs) and their derivatives, which possess remarkable light yield and X-ray sensitivity. This comprehensive review delves into cutting-edge approaches for optimizing MHP scintillators performances by enhancing intrinsic physical properties and employing engineering radioluminescent (RL) light strategies, underscoring their potential for developing materials with superior high-resolution X-ray detection and imaging capabilities. We initially explore into recent research focused on strategies to effectively engineer the intrinsic physical properties of MHP scintillators, including light yield and response times. Additionally, we explore innovative engineering strategies involving stacked structures, waveguide effects, chiral circularly polarized luminescence, increased transparency, and the fabrication of flexile MHP scintillators, all of which effectively manage the RL light to achieve high-resolution and high-contrast X-ray imaging. Finally, we provide a roadmap for advancing next-generation MHP scintillators, highlighting their transformative potential in high-performance X-ray detection systems. Highlights: 1 The review highlights recent advancements in enhancing the intrinsic physical properties of metal halide perovskite scintillators, such as improving light yield and response times, to improve their X-ray detection performance. 2 It discusses innovative engineering strategies to effectively optimize radioluminescent light management for high-resolution X-ray imaging. 3 The problems encountered in the application of metal halides perovskites materials for X-ray detection are summarized, and the potential development direction in the future is prospected.